Pilot study comparing the effects of high dose THC to high dose psilocybin and placebo in the set and setting of a classic psychedelic therapy session - Frederick S. Barrett; David Wolinsky; Zach Daily; Joseph Ciancio; Kristy Arthur; Ryan Vandrey (Psychopharmacology, 2026)
Abstract Rationale Delta-9-tetrahydrocannabinol (Δ9-THC) has been reported to evoke psychedelic-like experiences at high doses in some individuals. However, the doses of Δ9-THC that occasion such effects and the phenomenology of these experiences are poorly understood. Objectives This brief report presents preliminary findings from a pilot human laboratory study that directly compared the acute effects of Δ9-THC and psilocybin under set (expectancy) and setting (context) conditions of a typical psychedelic clinical trial. Methods Four healthy adults (ages 31–47, 3 F) received oral administration of placebo, psilocybin (25 mg), and 25 mg Δ9-THC, and two of these participants also received 50 mg Δ9-THC, in a double-blind, placebo-controlled, within-subject crossover study. Δ9-THC was administered as either synthetic Δ9-THC (dronabinol) or a whole-plant cannabis distillate extract (89.9% Δ9-THC). Subjective effects, cardiovascular measures, and safety were monitored throughout each session. Participants were asked after each session what drug they thought they had received. Results 25 mg Δ9-THC in both forms yielded a subjective experience similar to 25 mg psilocybin. Dronabinol was mistaken for a classic hallucinogen by both a psychedelic-naïve and a psychedelic-experienced participant. Conclusions These preliminary data suggest that a 25 mg oral dose of pure, synthetic Δ9-THC can be mistaken for a classic hallucinogen, and that oral Δ9-THC can elicit a psychedelic-like experience under set and setting conditions of a typical psychedelic clinical trial. While limited by sample size, these initial results provide insights into the comparative psychopharmacology of Δ9-THC and psilocybin as well as the potentially substantial impact of set and setting on subjective effects of psychoactive drugs. Trial Registration: This trial was registered at ClinicalTrials.gov (NCT06772753) on January 13, 2025